2023
DOI: 10.1021/acs.energyfuels.3c01029
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Fracturing and Enhanced Recovery in Shale Reservoirs: Theoretical Analysis to Engineering Applications

Abstract: Shale reservoirs are extensively exploited using hydraulic fracturing, which forms multiple cracks that connect with the existing natural fractures to create a continuous path for the gas stored in the kerogen to flow to the production well. Apart from the tedious nature of hydraulic fracturing, the mechanism of the storage and flow of gas is equally complex since multiple phases and scales are involved. An accurate understanding of hydraulic fracturing coupled with a strategy of analyzing the flow and overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(13 citation statements)
references
References 246 publications
0
13
0
Order By: Relevance
“…Yang et al proposed the construction and application of a comprehensive research digital platform for oil and gas exploration and development, which greatly improves the solving efficiency of artificial intelligence recognition. In recent years, the ensemble Kalman filter (EnKF), ensemble smooth multiple data assimilation (ESMDA), random gradient approximation algorithm, Markov process, and other non gradient methods for historical fitting have been widely applied. At the same time, breakthroughs in machine learning and deep learning have also brought new ideas to artificial intelligence recognition. Artificial intelligence uses the EnKF method to assist in automated history fitting, and by establishing a reservoir model, set the parameters that need to be fitted. Based on the EnKF method combined with production performance data, reservoir parameter inversion and reservoir simulation optimization are achieved, greatly improving the fitting accuracy. This method greatly reduces the workload of reservoir engineering personnel and simplifies the history fitting workflow. However, the upstream development of China’s petroleum industry still faces challenges…”
Section: Research Progress In Artificial Intelligence Technologymentioning
confidence: 99%
“…Yang et al proposed the construction and application of a comprehensive research digital platform for oil and gas exploration and development, which greatly improves the solving efficiency of artificial intelligence recognition. In recent years, the ensemble Kalman filter (EnKF), ensemble smooth multiple data assimilation (ESMDA), random gradient approximation algorithm, Markov process, and other non gradient methods for historical fitting have been widely applied. At the same time, breakthroughs in machine learning and deep learning have also brought new ideas to artificial intelligence recognition. Artificial intelligence uses the EnKF method to assist in automated history fitting, and by establishing a reservoir model, set the parameters that need to be fitted. Based on the EnKF method combined with production performance data, reservoir parameter inversion and reservoir simulation optimization are achieved, greatly improving the fitting accuracy. This method greatly reduces the workload of reservoir engineering personnel and simplifies the history fitting workflow. However, the upstream development of China’s petroleum industry still faces challenges…”
Section: Research Progress In Artificial Intelligence Technologymentioning
confidence: 99%
“…Previous studies have shown that the gas–water relationship in tight reservoirs is diverse . It is pointed out that there are conventional gas–water distribution and gas–water countercurrent body distribution relationships in tight oil and gas basins. , It is difficult to explain this complex gas–water distribution relationship with a single genesis mechanism. …”
Section: Introductionmentioning
confidence: 99%
“…Among them, shale gas reservoirs have great potential for exploration and development in a way they can unlock billions of cubic feet of gas. Multistage hydraulic fracturing is the main stimulation technique, , widely applied for economic gas extraction from such ultra-tight reservoirs. Water has remained the main source of hydraulic fracturing fluid (HFF), which has successfully been used to increase tight gas and shale gas recovery among different fracturing methods. However, shale formations are highly prone to blockage by water due to the contribution of nanopores to the texture of rock.…”
Section: Introductionmentioning
confidence: 99%